Implementation of Good Corporate Governance (GCG) Sharia in Maintaining the Sustainability of Commercial Banks in Indonesia - Maulida, Reska; Safira, Isti; Fuadi, Fatih; Iqbal, Muhammad (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the causal relationship between the implementation of Sharia good Corporate Governance and the long-term operational resilience of Sharia commercial banks, as well as integrating Islamic ethical concepts such as Ihsan and Maqashid Sharia into GCG performance measurement models. This study uses a normative-juridical-qualitative approach that is reinforced by quantitative-descriptive content analysis. The normative approach focused on the evaluation of the regulatory framework and the theological foundation, while the empirical analysis referred to the data of Sharia commercial banks operating in Indonesia for the period 2014-2023. Research shows that effective implementation of Sharia GCG contributes significantly to profitability (ROA) and operational resilience. The Sharia Supervisory Board (DPS) serves as a pillar of integrity with strict legal accountability. Banks that apply the Ihsan principle perform voluntary disclosure, which creates superior Trust Capital. However, the main challenge lies in the substantive implementation due to personal involvement and cultural challenges such as mental corruption. Good Sharia Corporate Governance is a non-negotiable prerequisite for the sustainability of Sharia commercial banks in the financial, ethical, and social dimensions. The effectiveness of Sharia Good Corporate Governance positions the bank to meet the dual objectives of mundane and ukhrawi accountability, with ethical transparency and Islamic Social Reporting (ISR) reporting as an important instrument in maintaining stakeholder trust.